Bitcoin Versus Gold Investment Performance During Covid-19 Recovery Period - Meikelwis Wijaya; Indah Melati (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study examines the comparative investment performance of Bitcoin and gold during the COVID-19 recovery period from March 2020 to December 2024. Using daily price data, the research employs Return on Investment analysis and ARCH- GARCH volatility modelling to assess the risk-return characteristics of both investment instruments during this critical economic period. The analysis reveals fundamental differences between the assets. Bitcoin exhibited average daily returns of 0.18% compared to gold's 0.04%, while demonstrating volatility 3.10 times higher than gold. ARCH-GARCH modelling confirms distinct volatility dynamics, with Bitcoin showing high volatility persistence indicating clustering effects, while gold demonstrates minimal persistence with no GARCH effects, reflecting stable characteristics. Five research hypotheses were tested and supported. Bitcoin demonstrated superior ROI performance but with substantially higher volatility than gold. GARCH models provided superior fit compared to ARCH specifications for both assets. The analysis reveals significantly different risk-return profiles, positioning Bitcoin as a high-risk, high-return asset suitable for risk-tolerant investors, while gold maintains its role as a stable portfolio diversifier. The findings demonstrate that Bitcoin and gold serve complementary rather than competing roles in investment portfolios during crisis periods. The results provide quantitative evidence for investment decision-making between traditional and digital assets, contributing valuable insights to cryptocurrency investment literature during unprecedented market conditions.